(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
This article explores the significance of developing digital literacy among listeners within the framework of professional development. Digital literacy has become an essential skill set in today’s technology-driven world, and it plays a pivotal role in the success of individuals across various industries. The article discusses the importance of digital literacy, provides an overview of effective methods for enhancing digital literacy, presents the results of implementing these methods, and offers a comprehensive discussion on the implications and future directions. The article concludes with key recommendations for fostering digital literacy among listeners and optimizing their professional development.